A review of blockchain technology application on supply chain risk management. Issue 10 (2022) - Hu, Yang; Ghadimi, Pezhman
Abstract: The purpose of this review is to investigate the landscape of scientific literature in analyzing the blockchain technology capabilities for enhancing supply chain resilience in times of increased risk and uncertainty. This article adopts a systematic literature analysis to extract and analyze the related papers. It is found that the blockchain technology can be considered as enabling technology for supply chain risk management. It helps to manage different types of risks in different industries, leading to resilience and robustness of a supply chain. This review also suggested that new research methodology, wider industrial adoption and combined implementation of blockchain and other advanced technologies can be investigated in the future to reduce supply chain risk more efficiently and effectively.